2013
DOI: 10.1051/0004-6361/201118362
|View full text |Cite
|
Sign up to set email alerts
|

The Hercules-Lyra association revisited

Abstract: Context. The Hercules-Lyra association, a purported nearby young moving group, contains a few tens of zero age main sequence stars of spectral types F to M. The existence and the properties of the Her-Lyr association are controversial and have been discussed in the literature. Aims. The present work reassesses the properties and the member list of the Her-Lyr association based on kinematics and age indicators. Many objects form multiple systems or have low-mass companions and so we need to properly account for… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
40
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 88 publications
6
40
1
Order By: Relevance
“…Placing these measurements in the context of other stars, similar variations have been observed in the long-term monitoring of the active Sun-like star ξ Boo A (∼4-9 G, Age: ∼0.2 Gyr, Mamajek & Hillenbrand 2008;Morgenthaler et al 2012), the K-dwarf exoplanet host Eri (∼10-12 G, Age: ∼0.2-0.8 Gyr, Janson et al 2008;Jeffers et al 2014b), and more recently for the young solar analogue HN Peg (∼14 G, Age: ∼0.2 Gyr, Eisenbeiss et al 2013;Boro Saikia et al 2015). The chromospheric and X-ray activity levels of these stars are also very similar to HD 1237.…”
Section: Summary and Discussionsupporting
confidence: 76%
“…Placing these measurements in the context of other stars, similar variations have been observed in the long-term monitoring of the active Sun-like star ξ Boo A (∼4-9 G, Age: ∼0.2 Gyr, Mamajek & Hillenbrand 2008;Morgenthaler et al 2012), the K-dwarf exoplanet host Eri (∼10-12 G, Age: ∼0.2-0.8 Gyr, Janson et al 2008;Jeffers et al 2014b), and more recently for the young solar analogue HN Peg (∼14 G, Age: ∼0.2 Gyr, Eisenbeiss et al 2013;Boro Saikia et al 2015). The chromospheric and X-ray activity levels of these stars are also very similar to HD 1237.…”
Section: Summary and Discussionsupporting
confidence: 76%
“…Again, we find that 2MASS J0213+3648 AB does not match any known young moving groups and lies outside the loosely defined young ( 125 Myr) Local Association (Zuckerman & Song 2004). We also found that 2MASS J0213+3648 AB did not match the kinematics of other groups not shown in our plot: Octans (Murphy & Lawson 2014), Hercules-Lyra (Eisenbeiss et al 2013), 32 Ori (Mamajek 2006), Carina Near (Zuckerman et al 2006) and Ursa Majoris (King et al 2003).…”
Section: The Age Of 2mass J0213+3648 Abcontrasting
confidence: 55%
“…Where no uncertainty is quoted, the uncertainty is set at 50 mÅ. This matches the limits of several major papers reporting lithium, including Eisenbeiss et al (2013), Kraus et al (2014b), and Rodriguez et al (2013); the largest upper limits reported by Malo et al (2013) and Moór et al (2013) are 46 mÅ.…”
Section: Lithium Samplementioning
confidence: 70%
“…3. Eisenbeiss et al (2013) conducted an analysis of Her-Lyr using gyrochronology, isochrone fits, lithium abundances, and chromospheric activity, concluding with the identification of seven "canonical" members, which we adopt as bona fide members. 4.…”
Section: Initial Member Datamentioning
confidence: 99%